Dwelling, human corporeity in liminal spaces: a study about forms of subjectivity in a slum - Tavares, Sandra Maria Greger; Albertini, Paulo (Paidéia (Ribeirão Preto), 2005)
This research adressed the experience of subjectivity construction and revelation in dwelling spaces in a frontier community at slums - a liminal space characterized by social, existencial and geographical instability - in São Paulo A three-year participant observation was made. Statements were obtained focusing on the history of the community and space transformation. Results have shown that slum dwellers, most of them northeast migrants, are between two manners of being and dwelling in the destination society, having two reference societies: the native and the destination one, living in a kind of "gap" since they have been excluded from dominant ways of space occupation and included in spaces in-between. Hybrid forms of subjectivity, dwelling and corporeity, experiences of establishment and dissolution, solidary and perverted strategies of inclusion, the important role of women regarding the organization of spaces and the pertinent relation between subjectivity, dwelling and corporeity were also constacted.